Renewable energy technology integration for the island of Cyprus: A cost-optimization approach. (15th October 2017) - Taliotis, Constantinos; Taibi, Emanuele; Howells, Mark; Rogner, Holger; Bazilian, Morgan; Welsch, Manuel
Abstract: In light of the ongoing financial crisis, Cyprus is called to transform its energy sector. The high electricity cost has been recognized as a priority issue and authorities on the island are considering several available options to reduce electricity tariffs. A fuel switch from oil to gas, domestic or imported, an electrical cross-border interconnection and a rapid increase in the share of renewable energy are among the major options being considered. Focusing on the power supply of Cyprus, the present study uses a cost-optimization tool to investigate the impact of different combinations of policy decision, resulting in a series of different scenarios, with some common key findings, with the aim of directly informing future energy policy decisions. Results indicate that renewable energy technologies will play a major role regardless the decisions taken. However, a set of enabling regulatory and market changes on the horizon might prevent least-cost deployment of renewables to take place. This study will review the findings and make some recommendations on the achievement of this optimal pathways for the evolution of Cyprus electricity sector. Highlights: Renewable energy technologies are currently cost-competitive in Cyprus. Transmission-connected solar PV is already the most competitive generation option. Price of natural gas may affect the share of renewable energy. Investments and political decisions are called for immediately. The analysis will assist in revising the Renewable Energy Action Plan of Cyprus.